Wood Drying Method by “Teresan” Process on Sengon Wood (Paraserianthes falcataria L. Nielsen) - Yoyo Suhaya; Bambang Subiyanto; Yoshinori Kobayashi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
This research aims to confirm the effect of conventional teresan process as a natural drying on Sengon (Paraserianthes falcataria L. Nielson) standing trees, and to develop a new teresan process by adding Arboricide.The experiment was done in dry season at Kuningan, West Java.  For the conventional teresan process, living trees were nicked into the cambial layer around the trunk at 15 ~ 25 cm in height from the ground. For the new teresan process, 25% percent kerosene solution of Arboricide Garlon 480EC was coated at the nick of the tree.Living Sengon trees in dry season showed high moisture content, i.e. around 60 ~ 100%.  By the conventional teresan process, the reduction of moisture was almost the same as control trees.  On the other hand, by the new teresan process coating with 25% kerosene solution of Arboricide Garlon 480EC it showed a large reduction of moisture content from over 100% to 30% in 4 months.  The new teresan process showed the drying speed of 0.66% per day; higher than that of the conventional process, i.e. 0.24% per day.  The new teresan process could be suggested as a high-speed natural drying method in the forest.